Determinants of Credit Growth and Interest Margins in the Philippines and Asia - Tan, Tatum Blaise Pua. (Washington, D.C. : International Monetary Fund, 2012)
Despite robust deposit growth, credit growth has been sluggish in the Philippines. We attribute this to legacy weaknesses in bank balance sheets, consumption-led economic growth, and relatively high net interest margins. Bank-level analysis suggests that interest margins in the Philippines rise with bank size, bank capitalization, foreign ownership, overhead costs and tax rates. Using bank-level data for a number of Asian economies, we find that higher growth, lower inflation, higher reserve requirements, greater banking sector development, smaller stock market development and lower government deficits reduce net interest margins, informing the policy debate on strengthening financial intermediation in the Philippines.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet